2009
DOI: 10.1159/000210574
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Losartan Pretreatment in an Experimental Model of Ischemic Acute Kidney Injury

Abstract: Background/Aims: Contributions to the understanding of acute renal failure (ARF) pathogenesis have not been translated into an effective clinical therapy. We studied the effects of pretreatment with the angiotensin II type 1 (AT1) receptor blocker, losartan, on renal function, tissue injury, inflammatory response and serum aldosterone levels in a model of ischemic ARF. Methods: Rats underwent unilateral renal ischemia followed by 24 h of reperfusion (IR), and were pretreated or not with 8 (IRL8) or 80 (IRL80) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 70 publications
(52 reference statements)
1
40
0
Order By: Relevance
“…Studies in animal models of AKI render data in support of the notion that kidney renin-angiotensin system (RAS) activation contributes to the pathogenesis of AKI [150][151][152][153]. An increase in urine AGT is now considered as one of the most promising biomarkers of AKI progression in patients with acute decompensated heart failure [46,55,154,155].…”
Section: Urine Angiotensinogenmentioning
confidence: 99%
“…Studies in animal models of AKI render data in support of the notion that kidney renin-angiotensin system (RAS) activation contributes to the pathogenesis of AKI [150][151][152][153]. An increase in urine AGT is now considered as one of the most promising biomarkers of AKI progression in patients with acute decompensated heart failure [46,55,154,155].…”
Section: Urine Angiotensinogenmentioning
confidence: 99%
“…An unexplored area is the potential therapeutic benefit of shunting the RAS pathway from activation of angiotensin II receptor type 1 by angiotensin II to activation of the Mas receptor by angiotensin 1-7. Pretreatment with angiotensin-converting enzyme inhibitors, angiotensin receptor blockers, and aliskiren has been shown to mitigate renal ischemia-reperfusion injury in experimental models, primarily by reduction in postreperfusion inflammation (66)(67)(68). Additionally, one study reported a reduction in the severity of AKI at 48 hours postreperfusion when captopril was continuously administered through an intraperitoneal osmotic micropump implanted immediately after renal ischemia-reperfusion injury.…”
Section: Angiotensinogenmentioning
confidence: 99%
“…The increase in uAGT in AKI is of interest, because it likely reflects local activation of the RAS within the kidney. Studies in animal models of AKI provide evidence in support of the concept that activation of the kidney RAS contributes to the pathogenesis of AKI (13)(14)(15)(16).…”
mentioning
confidence: 75%
“…Patients with AKI likely have a substantial inflammatory response (8), in part, caused by angiotensin II. Of note, in rodents exposed to renal I/R injury, RAS blockade using an ACE inhibitor or an angiotensin II type 1 receptor antagonist ameliorated inflammation within the kidney and alleviated the severity of AKI (13,14) This is not to say, of course, that blocking the proinflammatory and therefore, deleterious effects of RAS activation will overcome the generally considered beneficial hemodynamic actions of angiotensin II that help maintain systemic BP and attenuate the fall in GFR that occurs in AKI associated with decompensated heart failure.…”
mentioning
confidence: 99%